2017
DOI: 10.1097/hrp.0000000000000138
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Virtual Reality Technology in the Treatment of Anxiety and Other Psychiatric Disorders

Abstract: Virtual reality, or VR, allows users to experience a sense of presence in a computer-generated three-dimensional environment. Sensory information is delivered through a head mounted display and specialized interface devices. These devices track head movements so that the movements and images change in a natural way with head motion, allowing for a sense of immersion. VR allows for controlled delivery of sensory stimulation via the therapist and is a convenient and cost-effective treatment. The primary focus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
385
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 580 publications
(404 citation statements)
references
References 98 publications
4
385
0
15
Order By: Relevance
“…Age (years) 31 In the intervention group, 20 women (80%) indicated that they would use the VR again in a subsequent ECV procedure and 19 (76%) believed it should be offered as a routine part of the ECV. Twenty-two women (88%) said that they would recommend it to a friend undergoing ECV.…”
Section: Results For Control (N = 25) P-valuementioning
confidence: 99%
“…Age (years) 31 In the intervention group, 20 women (80%) indicated that they would use the VR again in a subsequent ECV procedure and 19 (76%) believed it should be offered as a routine part of the ECV. Twenty-two women (88%) said that they would recommend it to a friend undergoing ECV.…”
Section: Results For Control (N = 25) P-valuementioning
confidence: 99%
“…In addition to specific phobias, a recent review of VR research shows that this modality is a promising intervention used in the treatment of a variety of mental health concerns, including social anxiety, posttraumatic stress disorder (PTSD), panic disorder, generalized anxiety disorder, obsessivecompulsive disorder, schizophrenia, acute and chronic pain, addictions, eating pathology, and autism (Maples-Keller, Bunnell, Kim, & Rothbaum, 2017). As these applications gain traction, an increasing number of companies are beginning to create VR systems that interface with various bioand neuromodulation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…VR has been used to assess and treat a wide variety of medical, surgical, psychiatric, and neurocognitive conditions including pain [1,2,4,9,13,18], addiction [20][21][22][23][24][25], anxiety disorders [3,6,7,15,[26][27][28][29][30][31][32][33][34][35], schizophrenia [10,11,[36][37][38][39][40], eating disorders [1,[41][42][43][44][45][46][47][48], stroke rehabilitation [5,16,[48][49][50][51], vestibular disorders [52], and movement disorders [53]<...>…”
Section: Introductionmentioning
confidence: 99%